2020
DOI: 10.5194/bg-17-6341-2020
|View full text |Cite
|
Sign up to set email alerts
|

Vertical partitioning of CO<sub>2</sub> production in a forest soil

Abstract: Abstract. Large amounts of total organic carbon are temporarily stored in soils, which makes soil respiration one of the major sources of terrestrial CO2 fluxes within the global carbon cycle. More than half of global soil organic carbon (SOC) is stored in subsoils (below 30 cm), which represent a significant carbon (C) pool. Although several studies and models have investigated soil respiration, little is known about the quantitative contribution of subsoils to total soil respiration or about the sources of C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Three subsoil monitoring observatories (distance about 60 m) were established in 2013 in Grinderwald (Leinemann et al., 2016). They are equipped with multi‐segment suction plates for soil solution sampling (25 × 25 cm, ecoTech Umwelt‐Meßsysteme GmbH, Bonn, Germany), with 16 squared segments (36 cm 2 ) each, installed at 10, 50, and 150 cm soil depth (Leinemann et al., 2016), suction cups, and CO 2 sensors at 10, 30, 50, and 90 cm soil depth for analysis of soil CO 2 concentration profiles in combination with closed chambers for measurement of total soil CO 2 efflux (Wordell‐Dietrich et al., 2020) (Figure S1A). A field labeling approach was performed on the 13.2 m 2 circular catchment area of each of the three monitoring observatories by replacing the natural litter layer on 50% (i.e., 6.6 m 2 per observatory) of the area with 13 C‐enriched litter (Figure S1B), the other 50% remained unlabeled.…”
Section: Methodsmentioning
confidence: 99%
“…Three subsoil monitoring observatories (distance about 60 m) were established in 2013 in Grinderwald (Leinemann et al., 2016). They are equipped with multi‐segment suction plates for soil solution sampling (25 × 25 cm, ecoTech Umwelt‐Meßsysteme GmbH, Bonn, Germany), with 16 squared segments (36 cm 2 ) each, installed at 10, 50, and 150 cm soil depth (Leinemann et al., 2016), suction cups, and CO 2 sensors at 10, 30, 50, and 90 cm soil depth for analysis of soil CO 2 concentration profiles in combination with closed chambers for measurement of total soil CO 2 efflux (Wordell‐Dietrich et al., 2020) (Figure S1A). A field labeling approach was performed on the 13.2 m 2 circular catchment area of each of the three monitoring observatories by replacing the natural litter layer on 50% (i.e., 6.6 m 2 per observatory) of the area with 13 C‐enriched litter (Figure S1B), the other 50% remained unlabeled.…”
Section: Methodsmentioning
confidence: 99%
“…The incubation temperature of 20 • C should, therefore, be considered to be above the typical mean temperatures in the subsoils. For subsoils with comparable climatic conditions, Wordell-Dietrich et al (2020) found temperatures at 150 cm depth ranging from 4 to 14.4 • C over a 2-year period. Assuming a Q 10 value of around two for the assumable difference (Hamdi et al, 2013), the respiration rate at typical subsoil temperatures would be roughly half that.…”
Section: Is Sedimentary Derived Organic Carbon Biodegradable?mentioning
confidence: 93%
“…To be able to compare OC stocks and contributions from GOC, it was decided to set the borders between the topsoils and subsoils at 0.3 m and the transition from subsoils to the sediments at 1.5 m. According to Richter and Markewitz (1995), this represents a common border for the transition from soil to sediment. The sediments were further subdivided into an upper and a lower part at a depth of 4 m. (Eckelmann et al, 2006) and later transferred to the World Reference Base (WRB, 2006). Depth transitions to the starting sediment were 82 cm for loess (Al + Bt + elCv), 72 cm for Miocene sand (Bv − ilCv), and 68 cm for Red Sandstone (ilCv 1 ).…”
Section: Chemical Analysis and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations